UNDERSTANDING OF TERMINOLOGICAL TRANSLATION ("Conference on Universal Science Research 2023", 2024)
Terminological translation plays a crucial role in facilitating effective communication and knowledge transfer within specialized domains. It involves the translation of technical and specialized terminology, which requires precision and accuracy to convey meaning accurately across languages. One of the key principles in terminological translation is the concept of equivalence, which ensures that terms in different languages have similar meanings and functions within specific domains. This article aims to explore the theme of equivalence in terminological translation, its significance, and its application within specialized domains.